Access to and supply of finance for enhancing dairy productivity - Wilkes, Andreas; Odhong’, Charles; Ndonga, Samuel; Sing’ora, Brian; Kenyanito, Lucy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
The dairy sector is the largest single sub-sector within Kenya‘s agricultural sector, contributing about 14% of agricultural GDP and 3.5% of total GDP. With population growth, urbanization and rising incomes, consumption demand for milk is projected to increase significantly. If this is met from domestic production, greenhouse gas emissions from the dairy sector will increase. A proposal is being developed for submission to the emerging sources of climate finance for a dairy Nationally Appropriate Mitigation Action (NA-MA) in Kenya that aims to promote low-emission development of Kenya’s dairy sector. One of the main proposed approaches to reducing GHG emissions from the dairy sector is to increase the productivity of dairy cows and lower the intensity of GHG emissions (kg CO2e per kg milk). Increasing productivity on smallholder farms will require improved access to technical extension and advisory services, improved market linkages through dairy cooperatives, and finance for investments by farmers and dairy cooperatives. This report assesses access to credit finance by smallholder farmers and cooperatives, and the supply of finance from financial institutions and other sources, and identifies potential modalities for increasing access to finance to enable investments by smallholder dairy farmers and dairy cooperatives. Although participation in informal financial institutions is prevalent, the vast majority of dairy farmers have never had a loan from a formal financial institution. Constraints include lack of a perceived need for a loan, fear of loss of assets, inability to repay, lack of collateral and/or lack of financial records/credit history. The limited visibility of farmers‘ financial track record, and awareness of production and market risks and hence higher transaction costs are key barriers for financial institutions in financing dairy producers. Among households that have had a loan from a formal financial institution, SACCOs are the most common source. Dairy cooperatives also use their own funds, and funds from SACCOs and commercial banks to finance capital investments and operating expenses, and some have established relationships with financial institutions to facilitate payments for milk intake as well as other inputs and services. Loans to the dairy sector by formal financial institutions constitute a very small proportion of total loans for most financial institutions, except for SACCOs with a strong farmer base. Compared to commercial banks, SACCOs are better placed to serve dairy farmers, and their loan products have lower interest rates and more flexible terms. However, SACCOs are constrained in their ability to utilize international sources of finance, such as climate finance, and commercial banks, which typically focus on small and medium enterprises, are better placed to meet the financial needs of dairy cooperatives. Concessional loans, credit guarantees and technical assistance are all relevant mechanisms for supporting financial services to the dairy sector. Financial institutions highlighted in particular the need for technical assistance with developing financial products suited to the dairy sector’s needs and with application of information and communication technologies to provide supply chain financing solutions. The dairy and financial sectors in Kenya are both areas of dynamic innovation. Further research should focus on identifying and evaluating existing financial innovations in the sector, and assessing the potentials for up-scaling. Although many innovations make use of the relatively better supply of data and in-formation for decision-making and structured supply chain relationships in the formal sector, the majority of dairy farmers supply informal milk value chains and have limited links with formal financial institutions. The financial relationships and potential for innovations to promote financial inclusion outside the formal dairy and financial sectors should be a focus for future research.